Pencemaran Pb dan Cd pada Hasil Perikanan Laut Tangkapan Nelayan di Sekitar Teluk Jakarta - Wahyuningsih, Tri (Prosiding KPSDA, 2015)
This research aims to determine the concentration of Pb and Cd in marine fisheries in the Bay of Jakarta, this research began in February-December 2014, the research sites in Jakarta Bay waters. The method used in this research is laboratory test. Sampling of marine fisheries conducted in two periods of time, which are West Monsoon and East Monsoon. Sampling was conducted by buying directly from the fishermen who operate around the Bay of Jakarta with 4 groups of marine fisheries, which are Crustacea, Pisces, Bivalvia and Cephalopoda, each sample was taken 3 replications (triplo). The fishery product that has been collected, then taken to ABICAL (Agro Based Industry Calibration And Analytical Laboratoris) Laboratory Bogor, to test the content of Pb and Cd. Research data is processed by using qualitative descriptive statics. Result of the analysis of the average content of Pb in marine fisheries in Jakarta Bay on East and West monsoon generally undetectable (<0,042), whereas the concentration of Cd found in all types of sample and the highest found in blood cockle (0,747 mg/kg). This situation indicates that Pb and Cd in marine fisheries of Jakarta Bay is still below the treshold set by SNI (2009) of 1 mg/kg. Based on the result of this research concluded that marine fisheries in Jakarta Bay has been accumulated by Cd although the levels are still below the theshold. This indicates the presistence of harmful heavy metal pollution affect the most vulnerable communities around the Jakarta Bay. For that, the government of Jakarta is expected to address flooding in the future, so that the pollutants from around Jabodetabek are not easily contaminate the Jakarta Bay.